Linda Carlson and volunteer packing collection items - Unidentified photographer (Colorado State University. Libraries, 2000)
Photograph of Curator, Linda Carlson, and unidentified volunteer packing collection items during a May 2000 storage upgrade project, funded by an Institute of Museum and Library Services grant. Several bins are sitting on a table.
Keywords: Fashion -- History; Fashion -- Exhibitions